Mitogen‐activated protein kinase inhibition augments the T cell response against HOXB7‐expressing tumor through human leukocyte antigen upregulation. Issue 2 (28th November 2022) - Komatsuda, Hiroki; Wakisaka, Risa; Kono, Michihisa; Kumai, Takumi; Hayashi, Ryusuke; Yamaki, Hidekiyo; Sato, Ryosuke; Nagato, Toshihiro; Ohkuri, Takayuki; Kosaka, Akemi; Ohara, Kenzo; Takahara, Miki; et al.
Abstract: Homeobox B7 ( HOXB7 ) is a master regulatory gene that regulates cell proliferation and activates oncogenic pathways. Overexpression of HOXB7 correlates with aggressive behavior and poor prognosis in patients with cancer. However, the expression and role of HOXB7 in head and neck squamous cell carcinoma (HNSCC) remain unclear. In this study, we observed that most samples from patients with oropharyngeal cancer and HNSCC expressed HOXB7 . As no direct inhibitor has been reported, we identified a potent peptide epitope to target HOXB7 ‐expressing tumors through immune cells. A novel HOXB7 ‐derived peptide epitope ( HOXB7 8–25 ) elicited antigen‐specific and tumor‐reactive promiscuous CD4 + T cell responses. These CD4 + T cells produced γ‐interferon (IFN‐γ) and had the direct ability to kill tumors through granzyme B. Notably, downregulation of HOXB7 using siRNA enhanced human leukocyte antigen class II expression on tumor cells by decreasing the phosphorylation of MAPK. Mitogen‐activated protein kinase inhibition augmented IFN‐γ production by HOXB7 ‐reactive CD4 + T cell responses without decreasing the expression of HOXB7 . These results suggest that combining HOXB7 peptide‐based vaccine with MAPK inhibitors could be an effective immunological strategy for cancer treatment. Abstract : MAPK inhibition augmented IFN‐γ production by HOXB7‐reactive CD4+ T cell responses. Combining HOXB7 peptide‐based vaccine with MAPK inhibitors could be an effective immunological strategy for cancer treatment.